Sew perfect pets 18 adorable fabric animals to make for your home - Rhiannon, Helen (Tunbridge Wells Search Press, 2019)
"In Sew Perfect Pets, 18 whimsical and imaginative animal-themed projects have been designed not only to add character and colour to your home, but also to serve as functional items that will last for years to come. Key techniques and basic materials are detailed at the beginning of the book, and all of the projects include easy-to-follow, step-by-step instructions. Templates for all the animals are provided on a fold-out sheet at the back of the book. For sewers of all abilities, bring a touch of playfulness and practicality to your home today with these fresh faux animals that you'll soon love as much as the real guys!"--Provided by publisher
Includes index
1 2
Keywords: Soft toy making -- Patterns; Soft toy making; Stuffed animals (Toys); Stuffed animals (Toys); Pattern books; Pattern books; Patterns